Cell Signals Influencing Hepatic Fibrosis - Min Cong; Keiko Iwaisako; Chunyan Jiang; Tatiana Kisseleva (International Journal of Hepatology)
Liver fibrosis is the result of the entire organism responding to a chronic injury. Every cell type in the liver contributes to the fibrosis. This paper first discusses key intracellular signaling pathways that are induced during liver fibrosis. The paper then examines the effects of these signaling pathways on the major cell types in the liver. This will provide insights into the molecular pathophysiology of liver fibrosis and should identify therapeutic targets.